(untitled) (LEARNing Landscapes, 2012)
Research documents the benefits of implementing pedagogical practices that foster creativity in order to prepare students for a changing future and to meet the needs of emergent bilingual learners. Designing pedagogical invitations that make room for creativity is especially urgent given educational policies in the United States which privilege decontextualized, standardized learning aimed at "testable" skills, often in opposition to more expansive multilingual and multimodal learning opportunities. The current study explores how multimodal literacy experiences grounded in bilingual learners’ sociocultural realities stimulated creativity and allowed students to demonstrate and practice their creative abilities.